The Crucifixion of Jesus: Torture, Sexual Abuse, and Scandal of the Cross: oleh David Tombs - Chandra, Fang Fang (Asosiasi Teolog Indonesia, 2023)
A book review of The Crucifixion of Jesus: Torture, Sexual Abuse, and Scandal of the Cross.